Perbandingan Hasil Belajar Metode Problem Based Learning dan Metode Problem Solving - Goval Mahendra; Usmeldi Usmeldi (Jurusan Teknik Elektro Fakultas Teknik Universitas Negeri Padang, 2023)
This research was conducted with the aim of knowing the comparison of student learning outcomes using the Problem-Based Learning and Problem-Solving methods in the Basic Electrical and Electronics learning material for class X TITL SMK N 2 Kota Solok. The type of research used is Quasi-Experimental Design with the Pretest Posttest Nonequivalent Control Group Design method. Data analysis techniques use the normality test and homogeneity test, then use the t-test hypothesis test to make a decision. The results of hypothesis testing were carried out using the t-test and the results obtained were that the count value was smaller than the t-table at a significant level of 5%. Thus, it can be concluded that there is no significant difference in student learning outcomes in learning Basic Electricity and Electronics with the Problem-Based Learning and Problem-Solving methods at SMKN 2 Kota Solok.